Analyzing the relationship between destination attributes and satisfaction of tourists who visit rathnapura district - Sumithra, N.K. (University of Jaffna, 2020)
Rathnapura is one of the leading districts in Sri Lanka. Also well known as gem city in the country with a lot of well-known attractions and lesser-known attractions available in the area. According to the primary survey, even though there is a high volume of arrivals to significant attractions, other areas are not popular among foreign tourists. Therefore, the study was conducted to identify tourists' demographic profile, determine the relationship between destination attributes and tourist satisfaction, identify the most significant destination attribute, and make recommendations to improve tourists’ satisfaction. For this quantitative research study, 100 foreign tourists who visit the Rathnapura area were selected as samples. The convenience sampling technique is used by the researcher. Both primary and secondary data were collected and analyzed by SPSS version 21. According to the findings, Accessibility, Amenities, and Accommodations create a weak positive relationship with tourist satisfaction. However, Attraction in the Rathnapura area creates strong positive relations with tourists’ satisfaction. It is suggested to develop accessibility with good internal transportation, infrastructure, and other services. The accommodation sector needs to be improved further by providing value for money, service quality, and accommodation facilities development. It is also important for public and private promotional activities to develop Rathnapura as a major tourist destination.
Keywords: Accessibility; Accommodations; Amenities; Attraction; Tourist satisfaction